2014
DOI: 10.1124/dmd.114.058529
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitors Inhibit Methotrexate Transport by Renal Basolateral Organic Anion Transporter hOAT3

Abstract: The coadministration of methotrexate (MTX) and proton pump inhibitors (PPIs) can result in a pharmacokinetic interaction that delays MTX elimination and subsequently increases the MTX blood concentrations. Human organic anion transporters (hOATs) are responsible for the renal tubular secretion of MTX and are thought to be involved in this drug interaction. The aim of this study was to evaluate the inhibitory potencies of PPIs on hOAT1 and hOAT3, which are the two isoforms of OATs predominantly expressed in kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 50 publications
(58 reference statements)
3
34
0
1
Order By: Relevance
“…On the other hand, although NSAIDs showed mild inhibition of OCT-mediated uptake, the level of inhibition was minor. In contrast, extensive studies of omeprazole and lansoprazole have reported the inhibition of renal OATs and DDIs with methotrexate (a substrate of OATs) in vitro and in vivo (27,28). We also suspected similar drug interactions based on our in vitro data, which showed that omeprazole and lansoprazole inhibited OAT1-and OAT3-mediated PAS uptake by more than 70%.…”
Section: Figmentioning
confidence: 39%
See 1 more Smart Citation
“…On the other hand, although NSAIDs showed mild inhibition of OCT-mediated uptake, the level of inhibition was minor. In contrast, extensive studies of omeprazole and lansoprazole have reported the inhibition of renal OATs and DDIs with methotrexate (a substrate of OATs) in vitro and in vivo (27,28). We also suspected similar drug interactions based on our in vitro data, which showed that omeprazole and lansoprazole inhibited OAT1-and OAT3-mediated PAS uptake by more than 70%.…”
Section: Figmentioning
confidence: 39%
“…For the OCTs and OATs, we simply calculated the drug-drug interaction index using the equation C max /IC 50 , where C max indicates the maximum concentration and C max,u indicates the maximum unbound concentration of the inhibitor present in the systemic circulation (27,33,(39)(40)(41).…”
Section: Methodsmentioning
confidence: 99%
“…A recent study reported that hOAT3-mediated transport of methotrexate, which has a structure and pharmacokinetics similar to pemetrexed, was inhibited by PPIs (Chioukh et al, 2014). Several case reports and retrospective studies have demonstrated that coadministration of PPIs delayed the elimination of methotrexate (Suzuki et al, 2009;Santucci et al, 2010;Reeves et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…An estimated 20% of cancer patients have been treated with PPIs for alleviating the symptoms of gastroesophageal reflux (Smelick et al, 2013), highlighting the importance of investigating the drug interaction between PPIs and anticancer agents to provide safe and appropriate chemotherapy. Recent studies have reported that PPIs are inhibitors of hOATs and hOCTs (Nies et al, 2011;Chioukh et al, 2014). Since hematologic toxicity as a serious side effect of pemetrexed has been correlated with drug exposure (Rollins and Lindley, 2005), decreased clearance results in greater systemic exposure, which may be associated with increased side effects.…”
Section: Introductionmentioning
confidence: 99%
“…To relate our findings to clinical applications, we calculated the DDI index (22)(23)(24) according to the FDA guideline using the maximum concentration in plasma (C max ) and the unbound maximum concentration in plasma (C max,u ) (clinical pharmacokinetic data) (see Table S2 in the supplemental material) for each drug and the IC 50 for the prototype substrate and the clinically used substrate (zidovudine and metformin) from our in vitro study by plotting the equation mentioned in the FDA guideline and other reports to predict the possibility of a clinical DDI. Simply, we followed the method described by the FDA draft guidance and others: DDI index ϭ C max /IC 50 , where C max indicates the maximum concentration and C max,u indicates the maximum unbound concentration of the inhibitor present in the plasma (16,20,(23)(24)(25).…”
Section: Chemicalsmentioning
confidence: 99%